Ubiquitous Learning Based on LMS Moodle to Improve Self-Regulated Learning - Sujarwo; Safitri, Desy; Marini, Arita; Kusuma, Tubagus Ali Rachman Puja (Edukasi IPS, 2023)
Self-regulated learning (SRL) plays a pivotal role in fostering independent and lifelong learners. It empowers students to take control of their learning processes, enabling them to set goals, monitor their progress, and adapt strategies accordingly. Ubiquitous learning (U-Learning), on the other hand, emphasizes the seamless integration of learning experiences into everyday life through the pervasive presence of technology. This study aims to improve self-regulated learning and increase the learning independence of Universitas Negeri Jakarta students through ubiquitous learning based on the LMS Moodle. This study used a quantitative descriptive method, with the research subjects being 40 students of the social studies education program at Jakarta State University. In addition, Moodle is a powerful tool for implementing ubiquitous learning and improving self-regulated learning practices. By capitalizing on the platform's features and leveraging its potential, educators can create dynamic learning environments that empower students to take ownership of their learning journey. Future research and implementation studies should focus on exploring the effectiveness of Moodle-based ubiquitous learning strategies in diverse educational contexts to further enhance self-regulated learning outcomes.